Redo-Transcatheter Aortic Valve Replacement: Strategies When the First Transcatheter Aortic Valve Replacement Fails - Nils Perrin; Anita W Asgar (US Cardiology Review)
Transcatheter aortic valve replacement (TAVR) is the standard of care for patients with symptomatic severe aortic stenosis at high or prohibitive surgical risk. The 2020 valvular heart disease guidelines from the American College of Cardiology and American Heart Association now include TAVR as a class I indication for patients aged 65–80 years and not at high or prohibitive risk. The longer life expectancy of this patient population raises the issue of TAVR valve durability and the management of bioprosthetic valve failure of TAVR valves. In this review, the authors discuss bioprosthetic valve dysfunction and summarize existing data regarding redo-TAVR and surgery for failed TAVR. Finally, they propose an approach to evaluate patients with failed TAVR and plan for a second TAVR procedure as indicated.